Introduction to Compiler Construction in a Java World - Campbell, Bill; Iyer, Swami; Akbal-Delibas, Bahar (Chapman and Hall/CRC, 2013)
Immersing students in Java and the JVM, this text enables a deep understanding of the Java programming language and its implementation. It focuses on design, organization, and testing, helping students learn good software engineering skills and become better programmers.